TINJAUAN YURIDIS MENGENAI PEMBERHENTIAN PEGAWAI NEGERI SIPIL DIKARENAKAN MELAKUKAN PELANGGARAN, TINDAK PIDANA, DAN PENYELEWENGAN BERDASARKAN PERATURAN PEMERINTAH NOMOR 32 TAHUN 1979 TENTANG PEMBERHENTIAN PEGAWAI NEGERI SIPIL - Sabda Wibawa, I Putu; Palguna, I Dewa Gede (Kertha Negara : Journal Ilmu Hukum, 2014)
A rule about displacing of government civil servant is regulated in government rule number 32 year of 1979. There is a problem about displacing of government civil servant which is caused by doing a fault in government working rule system. Things which are often happened in civil servant system that is a civil servant break the rule in working time. So it needs to be followed up to. Writing method which used is normative legal research method, so that it is needed more review about this writing through government rule number 32 year of 1979. The conclusion that can be obtained from the journal is, displacing of government public served that do a fault, do a criminal and do a debauchery based on Article 23 par. (4) and (5) Act number 43 year of 1999 regarding Principles of Officialdom jo. Article 8, 9, 10 of government rule number 32 year 1979. In accordance with the article so that civil servants dismissed for a foul, criminal acts, fraud, punishable by imprisonment of 4 (four) years.
Keywords: rule, foul, criminal acts, fraud